2018
DOI: 10.7567/1882-0786/aaeedb
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in crystalline quality anisotropy for non-polar a-plane GaN directly grown on titanium patterned sapphire substrate

Abstract: Nonpolar a-plane GaN films were directly grown on titanium patterned sapphire substrates (Ti-PSS) by metalorganic chemical vapor deposition (MOCVD). It is demonstrated that the GaN film grown on Ti-PSS has superior surface quality and less surface pits than that on flat sapphire substrate. More importantly, the anisotropic behavior of the X-ray rocking curve-full width at half maximum values for the on-axis reflections were significantly improved. It is found that, the increased mosaic block size along m-direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In recent years, although many studies have been reported on the growth and characterization of the non-polar AlGaN materials [6,7], the non-polar AlGaN epi-layers grown on sapphire substrates still suffer from a high density of threading dislocations (TDs) and basal stacking faults (BSFs) owing to the large lattice mismatch between AlGaN epi-layer and the sapphire substrate [8,9]. To achieve high-efficiency non-polar AlGaN-based UV-LEDs, many approaches has been attempted to promote the crystal quality, such as using patterned sapphire substrates (PSSs), SiNx interlayers, and sidewall lateral epitaxial overgrowth (SLEO) [10][11][12]. Furthermore, AlInGaN quaternary alloys have been regarded as a promising material for AlGaN-based UV LEDs, because the energy band gap and the lattice constants of AlInGaN quaternary alloys can be adjusted independently by changing In and Al compositions [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, although many studies have been reported on the growth and characterization of the non-polar AlGaN materials [6,7], the non-polar AlGaN epi-layers grown on sapphire substrates still suffer from a high density of threading dislocations (TDs) and basal stacking faults (BSFs) owing to the large lattice mismatch between AlGaN epi-layer and the sapphire substrate [8,9]. To achieve high-efficiency non-polar AlGaN-based UV-LEDs, many approaches has been attempted to promote the crystal quality, such as using patterned sapphire substrates (PSSs), SiNx interlayers, and sidewall lateral epitaxial overgrowth (SLEO) [10][11][12]. Furthermore, AlInGaN quaternary alloys have been regarded as a promising material for AlGaN-based UV LEDs, because the energy band gap and the lattice constants of AlInGaN quaternary alloys can be adjusted independently by changing In and Al compositions [13,14].…”
Section: Introductionmentioning
confidence: 99%